Study on the mechanism of Buzhong Yiqi Decoction in the treatment of rectal prolapse: related analysis of single-cell transcriptome sequencing based on surgical excision specimens - Chen Huaxian; Xiao Guozhong; Liu Fang; Lin Hongcheng (结直肠肛门外科)
[Objectives] Buzhong Yiqi Decoction combined with surgery has good clinical efficacy in the treatment of rectal prolapse, but the mechanism of Buzhong Yiqi Decoction is not clear. This is a preliminary study to investigate the molecular mechanism of Buzhong Yiqi Decoction in the treatment of rectal prolapse. [Methods] The clinical data of 30 patients with rectal prolapse who underwent transperineal surgery at Department of Colorectal Surgery, The Sixth Affiliated Hospital, Sun Yat-sen University from January 2018 to September 2022 were retrospectively analyzed. 10 patients who had taken Buzhong Yiqi decoction were selected as the treatment group. 20 patients who received transperineal surgery only were matched according to age and sex using propensity matching scoring method as the control group. The clinical indicators of the two groups were compared and analyzed. One patient in each group was selected as the sample source for analysis, and the related analysis of single-cell transcriptome sequencing was performed. [Results] The effective rate was 100% in the treatment group and 80% in the control group. After treatment, Longo ODS score in the treatment group was lower than that in the control group (P=0.034). The two groups differ significantly regarding the change in Longo ODS score and Wexner anal incontinence score before and after treatment (P=0.030, P=0.046). Related analysis of single-cell transcriptome sequencing showed that compared with the control group, the proportion of fibroblasts in the treatment group was higher, and the function of fibroblasts in the treatment group was more significant in promoting the formation of extracellular matrix and inhibiting the degradation of extracellular matrix. There are differences in the transcriptome of fibroblasts and smooth muscle cells between the two groups, involving a variety of genes and their related pathways, which may be related to cell biological behavior, cell function and cell activity. Smooth muscle cells and pericytes interact fibroblasts through PDGF-PDGFR ligand-receptor pairs, which were more highly expressed in the treatment group than in the control group. [Conclusion] For patients with rectal prolapse, taking Buzhong Yiqi decoction before surgery can improve the overall efficacy. The mechanism of Buzhong Yiqi decoction may be to promote the formation of extracellular matrix and inhibit the degradation of extracellular matrix, in which fibroblasts play an important role.